Functional and Molecular Changes of MSCs in Aging - Kuang, Wei; Xu, Xin; lin, Jiong; Cao, Yang; Xu, Yue; Chen, Lin; Jin, Liang; Tan, Jiali (Current Stem Cell Research & Therapy, 2015)
Mesenchymal stem cells (MSCs) are ideal candidates for different cellular therapies due to their simple isolation, extensive expansion potential, and low immunogenicity. For various therapeutic approaches, such as bone and cartilage repair, MSCs are expected to replace the damaged tissues by direct differentiation. However, age-related changes in MSCs lead to the loss of differentiation potential, loss of proliferation potential and increase in senescent cell numbers, which involve a steady loss of bone mass and frequently result in osteoporosis. In this review, we will introduce the characteristic and age-related changes of MSCs. In addition, we will also summarize the potential rescue mechanisms of age-related bone loss involved in differentiation regulation and proliferation regulation, including transcription factors, signal pathways, epigenetic regulation, and oxidative stress regulation.
Keywords: epigenetic regulation